Utilization of Religion in Rehabilitation of Prisoners in Lahore (Al-Qamar, 2022)
The current paper aims to explore the utilization of religious teachings by the rehabilitators of prisons. Furthermore, the study explains the coping mechanism of prisoners by using religion during the process of rehabilitation. The study laid its foundation of theoretical paradigm of Reformative Theory which focuses that the object which is being used for punishment should be for reformation of the criminals instead of giving punishment. The study was conducted using a broader interpretive research design through semi-structured interview guide. The population were the prisoners from the central prisons of Lahore. Considering the aim of the study, participants were recruited using purposive sampling. The police officials were gatekeepers for the study as researcher cannot directly access to the participants. To avoid any biasness, a clear criterion of participants was shared with the officials. The criterion included; the prisoners who have spent at least 6 months in rehabilitation and at least 18 months in prison, officials found active religious participation of the individuals. Considering, the participant selection criterion, the officials identified 6 participants, the collected data were transcribed into codes and themes then set in a chronological way by applying thematic analysis. All ethical considerations were made while collecting data including, anonymity, confidentiality and avoiding harm to participants and researcher. The findings of the study suggested that prisoners are actively and effectively using religion as coping tool to overcome the hardships of the prison. Religious teaching showed them the way to seek forgiveness of God and seek their reintegration into the daily process of the society.
Keywords: Importance of Religion; Prisoners; Religion; Rehabilitation; Utilization